Juridicic Review On Punishment For Hard Drinkers (Khamr) By Positive Criminal Law And Islamic Criminal Law - Safaruddin Harefa (Fakultas Syariah UIN Antasari, 2020)
Abstract: In the current millineal era, society is very fast because of the many shifts from what was once a manual, now more to the era of digitization. But technological advances do not always have a positive impact, sometimes even a negative impact. . This is a challenge for law enforcement officials to be able to create a response, especially in the liquor case. The problem of liquor is now hotly discussed in the community because of the negative impact that damages the drinker and damages the community, as well as causing more criminal crimes. . This paper is an analysis of how the criminal law is able to achieve the legal goals aspired to be analyzed from the study